INVESTMENT AND ECONOMIC SECURITY OF THE ENTERPRISE - Bondarchuk , N.V. (The actual problems of regional economy development, 2020)
The article is aimed at studying the importance of investment in ensuring the economic security of the enterprise. The purpose of the article is to study the importance of investment in the economic security of the enterprise and to study the main methods of determining effective investment projects that ensure the economic security of the enterprise as a whole. The research methods used in the process of writing the article involve the use of general scientific and empirical techniques of economics, based on a systematic approach. In addition, general research methods such as generalization and comparison were used in the process. It is proposed to understand investment security as a subsystem of economic security that prevents possible threats and provides an opportunity for effective investment in order to develop the enterprise. When deciding on the possibility of investing available resources, the company conducts a thorough analysis of the available opportunities and possible risks associated with such activities. In the course of the research a system of measures to ensure the investment security of the enterprise is proposed, among which are: information and analytical support of the investment design procedure; assessment of the ability to implement the project; pre-investment preparation; investment project management. It is stated that the evaluation of efficiency is carried out by calculating a system of indicators or criteria for the effectiveness of the investment project, among which the advantages and disadvantages of the methods: simple methods of investment evaluation and investment evaluation methods based on discounting. The practical significance of this article is that the research of investment security as a component of economic security of the enterprise will contribute to the stable operation of enterprises, as well as reduce the risks that arise in the process of their activities.